IMPLEMENTASI METODE nth LOAD BALANCING DENGAN BAHASA PEMROGRAMAN PHP PADA MIKROTIK MENGGUNAKAN INTERNET SERVICE PROVIDER STUDI KASUS: XL DAN TELKOMSEL - Ita Asriani; Muh. Yamin; LM Fid Aksara (semanTIK, 2019)
The development of computer network technology, especially internet networks (interconnection networking) is currently increasing. The development of technology in the internet network which is increasing is directly proportional to the increasing number of users (users) of the internet network itself. The need for the internet now becomes a basic necessity both for seeking information, data communication and personal communication making many companies and agencies that have integrated the internet network into business processes or work processes, but the limitation of large bandwidth rental costs is a lack of bandwidth can be used. One of the contributions of technology to improve this is to use two ISPs and make it as load balancing. The mechanism, which is the proxy router, will mark the package that wants to access the internet, then choose which ISP path to pass and equalize the load on the two ISPs. The Load Balancing method has provided optimal bandwidth, but load balancing cannot accumulate a large bandwidth of the two connections, because load balancing technique does not mean 1 + 1 = 2 but 1 + 1 = 1 + 1 and the application of nth Load Balancing method has divided the traffic load balanced at ISP 1 and ISP 2.Keywords—Load Balancing, nth, Bandwidth. DOI : 10.5281/zenodo.2652059